Development of Epoxyeicosatrienoic Acid Analogs with in Vivo Anti-Hypertensive Actions - Imig, John D.; Elmarakby, Ahmed; Nithipatikom, Kasem; Wei, Shouzou; Tuniki, Venugopal R. (Frontiers in Physiology, 2010)
Epoxyeicosatrienoic acids (EETs) contribute importantly to the regulation of vascular tone and blood pressure control. The purpose of this study was to develop stable EET analogs and test their in vivo blood pressure lowering effects in hypertensive rats. Using the pharmacophoric moiety of EETs, ether EET analogs were designed with improved solubility and resistance to auto-oxidation and metabolism by soluble epoxide hydrolase (sEH). Ether EET analogs were chosen based on their ability to dilate afferent arterioles and subsequently tested for blood pressure lowering effects in rodent models of hypertension. Initially, 11,12-ether-EET-8-ZE failed to lower blood pressure in angiotensin hypertension or spontaneously hypertensive rats (SHR). Esterification of the carboxylic group of 11,12–ether-EET-8-ZE prevented blood pressure increase in SHR when injected at 2 mg/day for 12 days (MAP Δ change at day 8 of injection was -0.3±2 for treated and 12± 1 mmHg for control SHR). Amidation of the carboxylic group with aspartic acid produced another EET analog (NUDSA) with a blood pressure lowering effect when injected at 3 mg/day in SHR for 5 days. Amidation of the carboxylic group with lysine amino acid produced another analog with minimal blood pressure lowering effect. These data suggest that esterification of the carboxylic group of 11,12–ether-EET-8-ZE produced the most effective ether-EET analog in lowering blood pressure in SHR and provide the first evidence to support the use of EET analogs in treatment of cardiovascular diseases.